Source Analysis of “Kitob As-Savod Al-A'zam” (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article talks about the role of Abulkosim Hakim Samarkandi from the scholars of the science of the word, who lived and worked in Samarkand in the 9th-10th century, the first manifestations of the doctrine of moturidism, his contacts with Imam Abu Mansur Moturidi and the essence of the work of the scientist's royal work As-savod al-A'zam, as well as the source analysis of the work.